2017
DOI: 10.1590/s1806-92902017001100001
|View full text |Cite
|
Sign up to set email alerts
|

Environment, facilities, and management of hospital pens in growing and finishing pig farms: a descriptive study

Abstract: -The objective of this study was to describe the housing system in the hospital pens on growing and finishing (GF) pig farms. This work was developed by using a questionnaire and was conducted between January and April, 2016. Forty-four GF commercial farms (a total of 41,111 animals) were involved, seeking to raise issues concerning the facilities of the hospital pens, environment, management, feeding and the reasons for transferring the animals to these accommodations. About 98% of the evaluated farms had, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The high occurrence of metal chains and tires has previously been verified in a smaller sample of Brazilian farms (Pierozan et al, 2017), and the low prevalence of straw and other substrates confirms that these materials have low acceptance among Brazilian producers, mainly because they are considered impractical (Hötzel et al, 2009). In Europe, a similar study in 2008 found that Dutch farms also used numerous metal chains as well as more sophisticated objects such as rubber or plastic balls (either suspended or placed on the floor), plastic or rubber pet toys, and organic materials such as wood, straw, and sawdust (Bracke, 2017).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The high occurrence of metal chains and tires has previously been verified in a smaller sample of Brazilian farms (Pierozan et al, 2017), and the low prevalence of straw and other substrates confirms that these materials have low acceptance among Brazilian producers, mainly because they are considered impractical (Hötzel et al, 2009). In Europe, a similar study in 2008 found that Dutch farms also used numerous metal chains as well as more sophisticated objects such as rubber or plastic balls (either suspended or placed on the floor), plastic or rubber pet toys, and organic materials such as wood, straw, and sawdust (Bracke, 2017).…”
Section: Discussionmentioning
confidence: 81%
“…Farms that house gestating sows in pens only or in crates and pens are predominant (Callegari et al, 2020). It is considered that Brazilian pig farms use objects (Hötzel et al, 2009;Pierozan et al, 2017), even empirically and arbitrarily, without considering the scientific precepts of the subject, and therefore, the characteristics described above may not be present, and the benefits of enriching the environment may not be attained.…”
Section: Introductionmentioning
confidence: 99%